The Effectiveness of Utilizing Unmanned Aerial Vehicle (Uav) Technology in Supporting Security Operations in the Indonesia–Malaysia Land Border Area - Sulendra, Agus Surya; Gabriel, Thomas; Alam, Tasdik Mustika (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study examines the effectiveness of utilizing Unmanned Aerial Vehicle (UAV) technology in supporting land border security operations along the Indonesia–Malaysia border. The research addresses the increasing complexity of transnational threats that challenge conventional surveillance methods and require adaptive defense strategies. The objective of this study is to analyze the contribution of UAVs to border security operations, identify implementation constraints, and formulate optimization strategies for sustainable utilization. A qualitative descriptive-analytical method was employed, with data collected through in-depth interviews, field observations, and document analysis involving military operational units, border security task forces, and local stakeholders in the Kalimantan border area. The findings indicate that UAVs significantly enhance early detection, real-time aerial surveillance, and tactical decision-making. However, their effectiveness remains constrained by limited operator capability, inadequate infrastructure, and restricted logistical and budgetary support. The study concludes that integrating UAV systems into command and control structures, improving operator competence, and strengthening intersectoral cooperation are essential to establishing a modern and adaptive border security system.